The Portuguese tourism market: A model - Silva, J. A.; Ferreira, M. A. M.; Filipe, J.; Coelho, M. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
In Portugal, tourism is one of the most important economic sectors. Recently, with the development of the global crisis, particularly reaching the southern European Countries, this sector has strengthened and reinforced its importance due to the important rents got by Portuguese regional and local agents. Consequently, this topic is now particularly relevant. In this study, factors explaining demand, supply and prices are discussed. At macroeconomic level, it is seen how they contribute to model the Portuguese tourism market. A relationship among the variables is analyzed and its modeling is represented mathematically. The model gives an important contribution to show the importance of these variables and relationships in the determination of macroeconomic aggregates in the Portuguese tourism market.